Comparing the concept of Rahn and debenture in Islamic finance perspective - Mohd Sharoni, Syairazi Muhammad Husni; Hassan, Rusni (International Research Centre of Islamic Economics and Finance (IRCIEF), 2018)
Debenture is one type of security adopted by Islamic bank in Malaysia for commercial and corporate customers. Same as rahn, debenture as security is not a stand-alone product but it is a supporting contract linked to financing contract. This paper aims to compare the concept of rahn and debenture in Islamic finance perspective. This paper adopted qualitative paper that adopts Shariah resolutions of Bank Negara Malaysia (BNM) and Accounting and Auditing Organization of Islamic Financial Institution (AAOIFI) as references. However, this paper does not conduct a specific case from any Islamic bank which only focusing on library research. This paper found that, debenture as security is one type of modern security instrument which is based on rahn contract where the similarity rate between rahn and debenture is 77% (10 out of 13 elements). From the analysis, it shows that AAOIFI Shariah Standard No. (39) on Mortgage and Its Contemporary Applications is more comprehensive than BNM Policy Document of Rahn. Out of 13 Shariah requirements, AAOIFI manage to have clear resolution on 85% (11 requirements) while BNM only highlighted 69% (9 requirements). Therefore, industry player should ensure that product structure and legal documentations of debenture are in compliance with rahn Shariah as highlighted by BNM and AAOIFI.